FEASIBILITY STUDY OF AGROTOURISM IN SIANTAN HILIR PEAT VILLAGE AGROTOURISM - Muftia, Dika; Dolorosa, Eva; Kurniati, Dewi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
The development of agrotourism in Indonesia often faces management issues. However, this can be addressed by conducting a feasibility analysis. This study aims to analyze the feasibility of agro-tourism business in Siantan Hilir Peat Village Agrotourism from non-financial and financial aspects. Such a study, which examines the feasibility of agro-tourism business from both financial and non-financial perspectives in a peatland area, has not been conducted before. The non-financial feasibility aspects examined include technical, managerial, market, and social aspects. Meanwhile, the financial aspects consist of NPV, IRR, Net B/C, Payback Period, and Sensitivity Analysis. This research employed data triangulation method and financial feasibility analysis formulas. The non-financial feasibility analysis in Siantan Hilir Peat Village Agrotourism reveals that the area is suitable for agro-tourism due to its fulfillment of all technical, managerial, market, and social criteria. Furthermore, based on the financial analysis, it is evident that the agro-tourism business in Siantan Hilir Peat Village Agrotourism is viable and can be further developed. This is evidenced by the calculation shows it meets all the investment criteria. Therefore, the recommendation is to continue the development and operation of agrotourism in Siantan Hilir Peat Village Agrotourism while considering the risk management, especially in handling income fluctuations, and the focus should be on providing good services and developing products to maintain visitor interest.